notes the individual activity, diet, and abundance of the ants Pogonomyrmex vermiculatus and Solenopsis gayi (Hymenoptera: formicidae) in a semiarid ecosystem of northern Chile - Medel, R.G.=700 1 Fuentes, J.E.
(Es, En)
Ilus., 10 ref.
Keywords: POGONOMYRMEX; DIETA; DINAMICA DE LA POBLACION; CHILE; HORMIGAS; REVISTA CHILENA DE ENTOMOLOGIA